ECOLOGY OF PLANT PARASITIC NEMATODES ASSOCIATED WITH GROUNDNUT IN KARNATAKA - K. KRISHNAPPA, A. ISHWARA BHAT AND (Indian Phytopathology, 2002)
Random survey in 10 groundnut growing districts of Karnataka revealed association of six major types of plant parasitic nematodes, Aphelenchus auenae, Aphelenchoides sp., Helicotylenchus multicinctus, Pratylenchus coffeae, Rotylenchulus reniformis and Tylenchorhynchus dubius. Root-knot nematode, which is a number one problem on groundnut in other parts of India and world, was not encountered in the present survey. Maximum number of parasitic nematodes were recorded from soil samples of eastern dry zone, red soil, under irrigated conditions; cv. TMV-2 with redgram as previous crops. The age of the crop was between 61 and 75 days, and time of sampling was from 16 to 30 March as against minimum parasites recorded in northern transition zone, mixed red and black soil, under rainfed conditions, when paddy was the preceeding crop and the age of the crop was from 91 to 105 days. Maximum number of parasites in root samples was recorded from eastern dry zone, red soil, under irrigated conditions, cv. TMV-2, when groundnut was the previous crop and the age of the crop was between 46 and 60 days, and time of sampling was from 1 to 15 October. The minimum number was found in southern dry zone, deep black soil and under rainfed conditions.